Construindo cônicas no Geogebra e explorando seu lugar geométrico através da demonstração - Cavalcante, Jefferson Felipe Albuquerque (2019)
The use of recreational resources demands the development of new teaching methods that, with the objective of facing the challenges imposed by technology to help in class, bring different didactic resources, among them is Geogebra. With the help of this software I will present different ways of constructing the conics using only circles, straight lines, semi-circles, straight segments and points, to show that the geometric place created by these elements is conical, performing the demonstrations algebraically and/or geometrically, making them more practical and easy to visualize with the support of the program, ready to be applied in the classroom, as the teacher prefers.In order to initiate the student in the investigative and deductive method of mathematics through the demonstrations, with the purpose of developing his or hers logical-mathematical reasoning.